Sexual Violence and Land Seizure (2012)
The Colombian armed conflict has affected the civilian population subjecting it to massacres, forced displace the State’s crossfire. The rural population in particular has been hardest hit by warfare and its collateral consequences, since the armed conflict is mostly present and fought in rural areas where the institutional State’s presence is weak or non-existent, or where the illegal armed groups are after strategically positions or specific assets, such as land, territory, illicit crops, and mines.1 According to the 2011 Human Development Report on Colombia, 75.5% of Colombian municipalities are rural, and 31,6% of the total population lives in them2 . The projected total population for 2012 is 46’581.823, therefore the estimated population living in rural areas is over 14 millions